Comparative investigation on the failure modes of natural kenaf/epoxy reinforced composite hexagonal tubes - Alkbir, M. F. M.; S., M. Sapuan; Nuraini, A. A.; Ishak, Mohamad Ridzwan (Trans Tech Publications, 2016)
This study aims to investigate failure mode response of woven natural kenaf/epoxy composite hexagonal tubes subjected to an axial and lateral quasi-static crushing test. The hexagonal composite tubes were prepared by the hand lay-up technique using a variety of hexagonal angles 40ο, 50 ο, and 60 ο. The result showed that hexagonal composite tubes under an axial compression test exhibited few failure modes such as, the transverse crack failure mode . Splaying failure mode and local buckling failure mode respectively, whereas the tubes under lateral test only exhibited longitudinal fracture.